Weakly-bound clusters of atmospheric molecules: infrared spectra and structural calculations of (CO2)n–(CO)m–(N2)p, (n, m, p) = (2, 1, 0), (2, 0, 1), (1, 2, 0), (1, 0, 2), (1, 1, 1), (1, 3, 0), (1, 0, 3), (1, 2, 1), (1, 1, 2). Issue 12 (10th March 2022) - Barclay, A. J.; McKellar, A. R. W.; Pietropolli Charmet, A.; Moazzen-Ahmadi, N.
Abstract : Structural calculations and high-resolution infrared spectra are reported for trimers and tetramers containing CO2 together with CO and/or N2 . Abstract : Structural calculations and high-resolution infrared spectra are reported for trimers and tetramers containing CO2 together with CO and/or N2 . Among the 9 clusters studied here, only (CO2 )2 –CO was previously observed by high-resolution spectroscopy. The spectra, which occur in the region of the ν 3 fundamental of CO2 (≈2350 cm −1 ), were recorded using a tunable optical parametric oscillator source to probe a pulsed supersonic slit jet expansion. The trimers (CO2 )2 –CO and (CO2 )2 –N2 have structures in which the CO or N2 is aligned along the symmetry axis of a staggered side-by-side CO2 dimer unit. The observation of two fundamental bands for (CO2 )2 –CO and (CO2 )2 –N2 shows that this CO2 dimer unit is non-planar, unlike (CO2 )2 itself. For the trimers CO2 –(CO)2 and CO2 –(N2 )2, the CO or N2 monomers occupy equivalent positions in the 'equatorial plane' of the CO2, pointing toward its C atom. To form the tetramers CO2 –(CO)3 and CO2 –(N2 )3, a third CO or N2 monomer is then added off to the 'side' of the first two. In the mixed tetramers CO2 –(CO)2 –N2 and CO2 –CO–(N2 )2, this 'side' position is taken by N2 and not CO. In addition to the fundamental bands, combination bands are also observed for (CO2 )2 –CO, CO2 –(CO)2, and CO2 –(N2 )2, yielding some information about their low-frequency intermolecular vibrations.